2021
DOI: 10.1007/978-3-030-85214-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Life Skills Education for Youth in Developing Countries: What Are They and Why Do They Matter?

Abstract: Drawing from a review of theoretical, methodological, and empirical literature on life skills from the fields of education, public health, psychology, economics, and international development, this paper attempts to clarify basic definitional and conceptual issues that relate to life skills education. It addresses the questions: (1) What are life skills, and how has the term emerged in academic and donor agency literature? And (2) What bodies of practice and research evidence converge in the rise of ‘life skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…This skill will contribute to health by helping individuals identify and assess factors that influence attitudes and behavior, such as values, peer pressure, and the media [15]. To promote health through life skills, individuals need to understand information or knowledge correctly and have cognitive skills so that they are able to think critically in every phase of their lives [13]. Individuals with higher critical thinking skills reported fewer negative life experiences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This skill will contribute to health by helping individuals identify and assess factors that influence attitudes and behavior, such as values, peer pressure, and the media [15]. To promote health through life skills, individuals need to understand information or knowledge correctly and have cognitive skills so that they are able to think critically in every phase of their lives [13]. Individuals with higher critical thinking skills reported fewer negative life experiences.…”
Section: Resultsmentioning
confidence: 99%
“…These cognitive life skills are processes that occur in every human brain and are influenced by the psychosocial competencies they already have, so they will help when a person has to think about deciding something in his/her life, including the decision to have sexual intercourse or remain abstinent. Adolescents with healthy cognitive skills will be able to think critically and make the right decisions regarding their health [13]- [16].…”
Section:  Issn: 2252-8806mentioning
confidence: 99%
“…Por ejemplo, estas habilidades se vinculan a la mejora del logro académico (Arias Ortiz et al, 2017;Marcos Sánchez y Diéz González, 2017;OECD, 2021a;Outes & Sánchez, 2017;Treviño et al, 2019); la reducción de la deserción (Heller et al, 2016); la disminución de la violencia (Heller et al, 2016;Ramos et al, 2007); y el incremento de la empleabilidad (Bassi et al, 2012;Cunningham et al, 2016;Kautz & Heckman, 2014;OECD, 2021a;Székely, 2015;The World Bank, 2011). Con la crisis por COVID-19, el bienestar socioemocional, la salud mental y las habilidades socioemocionales han recobrado mayor interés en la escuela como parte del desarrollo integral del niño, niña y adolescente, y se constituyen como parte esencial de la formación inicial y en servicio del docente (Murphy-Graham & Cohen, 2022;Unesco, 2021a).…”
Section: Introductionunclassified
“…Considerando esto, organizaciones internacionales han venido diseñando marcos de referencia para orientar el desarrollo y evaluación de estas habilidades (Arias et al, 2020;Ríos et al, 2022;Unesco, 2021a). No obstante, si bien existe un consenso sobre la importancia de las habilidades socioemocionales, este se disipa cuando se aborda su definición y terminología (Murphy-Graham & Cohen, 2022;Unesco, 2021a). Un reflejo se encuentra en los currículos nacionales.…”
Section: Introductionunclassified
“…Since secondary education is becoming more mainstream in developing countries, most life skills education programs target adolescents. [ 3 4 ] Considering that adolescence is a time of rapid biological, psychological, and social change, this is no surprise. A global evaluation of life skills education programs found that there is strong evidence that such programs develop relevant knowledge, skills, and attitudes among youth, both in thematic risk areas and in general psychosocial competence.…”
Section: Introductionmentioning
confidence: 99%